DBF8, an essential gene required for efficient chromosome segregation in Saccharomyces cerevisiae. - Houman, F (1994)
To investigate chromosome segregation in Saccharomyces cerevisiae, we examined a collection of temperature-sensitive mutants that arrest as large-budded cells at restrictive temperatures (L. H. Johnston and A. P. Thomas, Mol. Gen. Genet. 186:439-444, 1982). We characterized dbf8, a mutation that causes cells to arrest with a 2c DNA content and a short spindle. DBF8 maps to chromosome IX near the centromere, and it encodes a 36-kDa protein that is essential for viability at all temperatures. Mutational analysis reveals that three dbf8 alleles are nonsense mutations affecting the carboxy-terminal third of the encoded protein. Since all of these mutations confer temperature sensitivity, it appears that the carboxyl-terminal third of the protein is essential only at a restrictive temperature. In support of this conclusion, an insertion of URA3 at the same position also confers a temperature-sensitive phenotype. Although they show no evidence of DNA damage, dbf8 mutants exhibit increased rates of chromosome loss and nondisjunction even at a permissive temperature. Taken together, our data suggest that Dbf8p plays an essential role in chromosome segregation.